Penerapan Aplikasi Zahir Accounting dalam Penyusunan Laporan Keuangan pada PT. Mitra Flexitech Berdikari Jakarta - Nia Nuraeni; Asrie Putri Wulandari (Artikel Ilmiah Sistem Informasi Akuntansi, 2021)
In the process of processing accounting data at PT. Mitra Flexitech Berikari are still using manual recording. Manual accounting processing has more risk of error than using a computerized system. Thus, the author will apply the transaction system that has been done by PT. Mitra Flexitech Berdikari to the Zahir Accounting version 5.1 application to help make financial records easier because Zahir Accounting version 5.1 is a software that has a complete feature, with an attractive program design that is very easy to use and designed precisely for the needs of small and medium businesses in Indonesia. This study aims to implement and implement the Zahir Accounting version 5.1 application for recording all transactions at PT. Mitra Flexitech Berdikari to produce precise and accurate financial reports. The research method used by conducting direct observations at PT. Mitra Flexitech Berdikari and conduct a question-and-answer process with the leadership of PT. Mitra Flexitech Berdikari with related parties directly in the accounting data processing section so that the required information can be obtained besides that the author also conducts a literature study, namely the author conducts library research that is relevant to the problem at hand. After completion, it can be seen that the creation of Zahir Accounting V 5.1 in the financial system. So that the existing manual financial system can be replaced with a computerized sister system. The Zahir Accounting system designed aims to build a computerized accounting system that makes it easier for PT. Mitra Flexitech Independent in accounting procession